Reducing violence against women and girls - Hidrobo, Melissa; Roy, Shalini; Leight, Jessica; Heckert, Jessica (International Food Policy Research Institute, 2021)
Violence against women and girls (VAWG) is a global public health crisis and human rights violation, with adverse consequences for women and girls, economies as a whole, and future generations. Existing multicountry evidence suggests that the high prevalence of VAWG in low- and middle-income countries could be holding back advances in many priority areas — such as education (Gennari et al. 2014), health (Ellsberg et al. 2008), nutrition (Yount et al. 2011), adaptation to climate change (Le Masson et al. 2019), and adoption of sustainable livelihoods (Morrison and Orlando 2004). In the context of agricultural development, VAWG can reduce agency (Theis et al. 2018) — preventing women from seeking control over assets and income (instrumental agency), participating in groups (collective agency), and building self-worth (intrinsic agency). In addition, fear of sexual harassment and/or sexual violence in public spaces can induce girls or women to choose lower quality educational outcomes (Borker 2021), limit their opportunities for safe and decent work (Nordehn 2018), and depress their labor market participation (Chakraborty et al. 2018, Siddique 2021).